Er-doped fiber laser with regular and random distributed feedback. Issue 1 (1st April 2022) - Skvortsov, M.I.; Wolf, A.A.; Fomiryakov, E.A.; Treshchikov, V.N.; Nikitin, S.P.; Vlasov, A.A.; Dostovalov, A.V.; Babin, S.A.
Abstract: Using a point-by-point fs inscription technology, a Rayleigh reflector with unique characteristics has been designed and fabricated. The reflection coefficient of the structure with a length of 5 cm amounts to 0, 03%, which corresponds to the reflection of 6-km SMF-28e+ fiber spool. The designed artificial Rayleigh scattering fiber in combination with distributed feedback (DFB) erbium-doped fiber laser allows to narrow the linewidth. A similar effect was observed in configuration with 25-km SMF-28e+ fiber spool, where it was used as an additional spectral filter. In both cases, an identical narrowing of the linewidth by an order of magnitude was observed at times less than 0, 1 msec.